Correlation of Motor Competence and Social-Emotional Wellbeing in Preschool Children - Salaj, Sanja; Masnjak, Mia (Frontiers in Psychology, 2022)
Introduction The relations of motor skills to different developmental domains, i.e., cognitive, emotional, and social domain, are well-documented in research on children with poor motor competence and children with disabilities. Less conclusive evidence on interaction of motor and social or emotional development can be seen in research on typically developing children. The purpose of this study was to determine a correlation between motor skills and social-emotional functioning in typically developing preschool children and to identify differences in social-emotional functioning in children with different levels of motor competence. Methods A total of 125 preschool children (67 boys, 58 girls, average age 5.1 years) participated in this study. To assess children’s motor skills, we used the Test of Gross Motor Development–Second Edition that measures locomotor and object-control skills. To screen child’s social and emotional functioning, we used the Ages and Stages Questionnaire–Social Emotional: Second Edition. Spearman’s correlation analysis was used to determine association between motor skills and social-emotional functioning. Difference in social-emotional functioning between groups of preschool children with High and Low motor competences was calculated using Mann-Whitney U-test. Results The main result of this study is weak correlation of child’s motor skills to social-emotional functioning. Furthermore, preschool children with High and Low motor competences do not differ in risk for social and emotional difficulties. Conclusion Further research on typically developing children is needed to have more conclusive evidence on interaction of motor and social or emotional development.